(untitled) (Biological Sciences - PJSIR, 2022)
Proximate composition of seven varieties of sunflower seed and meal and their nitrogen solubility profile in water (20.5-22.5%),5% NaCI (49.6-52.8%) 70% C2 Hs OH (3.0-4.0%) and 0.2% NaOH (9.8-11.0%) was determined. In vitro digestibility of untreated and enzymic treated sunflower meal was found to be 34.5% and 83.5% respectively. The autoclaving of untreated meal at 1kg/em? for 5-60 mins., showed a gradual decrease in vitro protein digestibility from 34.5 to 12.0%. In vitro protein digestibility of enzymic treated meal increased from 83.5 to 87.2% after 15 mins. autoclaving. Further increase in autoclaving time to 60 mins showed a gradual decrease in the In vitro digestibility. Hence processing of sunflower meal at 1 kg/em? for 15 mins. was found most suitable.